Systematic Literature Review: Use of Augmented Reality as A Learning Media: Trends, Applications, Challenges, and Future Potential - Heydemans, Charnila; Elmunsyah, Hakkun (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2024)
This article conducts a systematic literature review (SLR) focusing on the application of Augmented Reality (AR) as an educational tool. The review process, guided by SLR and PRISMA methodologies, included steps such as identification, screening, eligibility assessment, inclusion, and data analysis, utilizing tools like Publish or Perish 8 and NVIVO 12 Plus. An initial search on Scopus produced 800 articles, which were subsequently narrowed down to 59 relevant studies. These were analyzed with NVIVO 12 Plus according to specific topics. The results indicate that AR effectively enhances students' academic achievement, interest, motivation, and participation across various subjects such as science, mathematics, languages, and engineering education. However, challenges include hardware and software limitations and insufficient technical training for teachers. AR holds great potential for improving learning experiences, particularly for students with special needs. Future developments should focus on affordable software and adequate teacher training to expand AR's educational use. Further research should explore AR in vocational education to better understand its specific requirements.